Impact of Online Learning During the Covid-19 Pandemic on the 'Paket C' Learning Program - Livia Astuti (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2021)
Every citizen has the right to education. One of the educational pathways in Indonesia is Non-Formal Education, such as Study Groups, courses, Learning Activity Studios, tutoring, training centres, and the like. Non-formal education students are usually called Learning Citizens, teachers for learning residents are called teaching tutors. Non-formal education has a flexible implementation, regulations, and a curriculum that focuses on one or a few lessons. Non-formal education emphasizes one or several studies to gain knowledge and skills in specific fields relatively quickly compared to formal education. The Covid-19 pandemic has not only hit Indonesia but the whole world. The order of education has changed, which was initially face-to-face, now it has to be online. Residents of learning and tutors are forced to operate online media for continuous learning. This study aims to analyze the positive and negative impacts of online or distance learning during the Covid-19 pandemic. The method used is Literature Study, data obtained by collecting library data from news, journals, magazines, theses, and books, then recorded and processed into research material. The study results show that online learning has a negative impact, namely the network is not adequate as a result, learning residents experience failure to understand. With the material presented, enthusiasm decreases; limited facilities in online learning; expensive internet quota. The positive impact of online education is that knowledge is more practical; delivery of material/information can reach large numbers; more interested in online, civil servants and learning residents gain new experiences. In general, there are more negative impacts than positive ones. So it needs further development research, focusing on the best online learning methods.